THE GRATITUDE AND MARITAL SATISFACTION IN THE INFERTILE SPOUSES - Suminta, Rini Risnawita; Ghufron, M. Nur (Psikis : Jurnal Psikologi Islami, 2022)
Marital satisfaction is one of the most important factors for achieving a happy family. This study aimed to examine the relationship between gratitude and marital satisfaction in infertile spouses . This study involves 44 samples of spouses who have been married for at least one year and have not had children in Kediri, East Java. The research was conducted by using convenience sampling technique. The data collection techniques used in this study were questionnaires in the form of scales. There were two types of scales used in the data collection process: the scale of marital satisfaction and the scale of gratitude. The data were analyzed by using correlation technique. Based on the results of the analysis, it was found that gratitude had a positive correlation with marital satisfaction with r = 0, 489; p = 0,001 meaning that the higher the gratitude of an infertile couple, the higher their marital satisfaction is.